2018
DOI: 10.1080/17475759.2018.1555673
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Receivers’ Nationality and Cultural Orientation on the Effects of Fear Appeals in Health Communication

Abstract: Participants from the Netherlands (n = 52), China (n = 50), and South Africa (n = 166) either read a self-targeted or a family-targeted fear appeal message about chlamydia. Seven aspects of individual cultural orientation were measured, and six effects of the different messages. Interactions between nationality and target of threat were found on perceived severity, perceived susceptibility, and danger control. Only for perceived susceptibility, a difference in cultural orientation partly explained this interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The result is consistent with Jansen and Kroef's (2019) study. The study also failed to investigate the interaction between self-targeted messages versus familytargeted messages on perceived severity, perceived susceptibility and perceived response efficacy, fear control, and danger control.…”
Section: Role Of Cultural Orientation In the Fear Appeal Processsupporting
confidence: 93%
See 1 more Smart Citation
“…The result is consistent with Jansen and Kroef's (2019) study. The study also failed to investigate the interaction between self-targeted messages versus familytargeted messages on perceived severity, perceived susceptibility and perceived response efficacy, fear control, and danger control.…”
Section: Role Of Cultural Orientation In the Fear Appeal Processsupporting
confidence: 93%
“…Some studies had failed to investigate the moderation effect of self-construal when an individual appraised different message type (self-interest focus versus otherinterest focus) (Jansen & van der Kroef, 2019;Jansen & Verstappen, 2014). This proposition's lack of replicability increases doubts about the self-construal effect on evaluating fear appeal components.…”
Section: Table Of Contents List Of Tables Pagementioning
confidence: 99%
“…Health communication concerns health education, risk communication, health literacy. Strategies in heath communication act to disseminate information that influences personal health behaviours and choices to be more committed to proper health procedures (Basch et al, 2020;Jansen & Van der, 2019). Bulunmaz (2019) defined health communication as the use of communication to promote healthy behaviours that protect citizens and society from diseases and infections.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…The present study was an exploratory analysis using a sample of countries that were culturally diverse, in line with past research recommending the inclusion of cultural composition when examining health behaviours, health communication and the development of public health policies (e.g. Jansen and van der Kroef, 2019 ; Singer, 2012 ). Thus, the effects on and of worry with respect to past and future health behaviours were investigated from a cross-cultural perspective.…”
mentioning
confidence: 90%
“…Research has also suggested that public health responses at the individual and national levels can be influenced by cultural orientations (e.g. Jansen and van der Kroef, 2019 ; Leijen and van Herk, 2020 ). More recently, Muthukrishna et al (2020) have developed a tool for measuring cultural distance – the extent to which countries exhibit differences in psychological and cultural characteristics, like Hofstede’s (1984) cultural dimensions, tightness-looseness of societies, Schwartz’s (2006) values and the Big Five personality traits, among others.…”
mentioning
confidence: 99%